Indonesia : Selected Issues. (IMF Staff Country Reports; Country Report, 2007)
This Selected Issues paper assesses Indonesia's trade integration relative to underlying country characteristics. The paper analyzes Indonesia's vulnerabilities, especially compared with the eve of the crisis in 1997. Various indicators suggest that the underlying fundamentals are significantly stronger. The paper examines key features of the financial safety net (FSN) in view of international standards and concludes that the current system is capable of timely addressing bank problems. It looks at determinants of, and constraints to, credit growth in recent years.